Sikap Respek Yesus terhadap Penyandang Disabilitas - Arcadius Benawa (Pedulidisabilitas Center, 2022)
The purpose of this study is to show that the notion of salvation actually influenced attitudes of human beings in relation to one another. Through the study of the Gospel of Luke, especially about Zacchaeus, it became clear that Jesus' attitude towards people with disabilities is very appreciative and respectful has a social impact that has extraordinary transformational power so that life is more meaningful and dignified for everyone, especially for the diffable. It is time for us to disseminate enlightening insights in human relations that uphold basic trust, namely that whoever and regardless of one's condition must be treated humanely